(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
The scale of internationalization of higher education in the CIS countries, along with the impact of this process on the socio-economic and cultural development of the regions, once again demonstrates the need for its close study, analysis of the experience of other countries, evaluation of the results of previous research in this area. Thus, this paper attempts to characterize the main trends in the development of research on the internationalization of higher education by comparing the competencies of the CIS countries with the EU countries and some Asian countries. The article also discusses the phenomenon of multidimensional integration processes in higher education, analyzes the main facts that affect the process of internationalization. The aim of the study is a theoretical and methodological analysis of the constructive experience of internationalization of the educational process in EU and CIS universities. Research methods: structural analysis and synthesis development of foreign researchers allowed to isolate in the complex phenomenon of internationalization of universities the basic elements that have a decisive influence on the nature of the object of study; methods of comparative analysis, that allowed to establish the similarities and differences between the processes of internationalization of universities in advanced foreign countries and Kazakhstan, as well as an integrated approach, allowing to consider the phenomenon of internationalization of universities in its relationships and dependencies with other processes and phenomena in the context of globalization. The results of the study can be defined within the conduct of case studies of internationalization of European universities and the findings of prominent researchers, and, on this basis, to identify the need of implementation of internationalization processes actually contributing to the development of the modern University, improving its competitiveness on the internal and external market of educational services and research.